2011
DOI: 10.1128/aac.01835-10
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Renal Tubular Secretion of the Antimalarial Drug Chloroquine

Abstract: The antimalarial drug chloroquine is eliminated to a significant extent by renal tubular secretion. The molecular mechanism of renal chloroquine secretion remains unknown. We hypothesized that organic cation transporter 2 (OCT2) and multidrug and toxin extrusion protein 1 (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 40 publications
2
48
0
Order By: Relevance
“…The major new findings of our investigations are the following: (1) Trimethoprim inhibits OCT2-, MATE1-, and MATE2-K-dependent transport of both metformin and NMN in vitro. Our data are in line with previous reports investigating in vitro inhibition of OCT2-and MATE1-dependent metformin transport by trimethoprim and are to the best of our knowledge the first to show that trimethoprim also inhibits NMN transport [19,21]. We estimate that mean unbound trimethoprim trough and peak plasma concentrations were ∼4 and 9 μM, respectively, in the healthy volunteers of our study (assuming f u =0.6).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The major new findings of our investigations are the following: (1) Trimethoprim inhibits OCT2-, MATE1-, and MATE2-K-dependent transport of both metformin and NMN in vitro. Our data are in line with previous reports investigating in vitro inhibition of OCT2-and MATE1-dependent metformin transport by trimethoprim and are to the best of our knowledge the first to show that trimethoprim also inhibits NMN transport [19,21]. We estimate that mean unbound trimethoprim trough and peak plasma concentrations were ∼4 and 9 μM, respectively, in the healthy volunteers of our study (assuming f u =0.6).…”
Section: Discussionsupporting
confidence: 93%
“…**p<0.01 vs. phase A/day 4 preferential MATE1 inhibition; for NMN: preferential MATE2-K inhibition) compared to inhibition of basolateral uptake via OCT2. Our previously reported IC 50 value for inhibition of MATE1-mediated metformin transport by trimethoprim [21] is in very good agreement with the respective K i value we determined in the present experiments (6.2 vs 6.3 μM). We previously reported that trimethoprim also preferentially inhibits MATE2-K-mediated lamivudine transport (IC 50 =0.66 μM) compared to OCT2-mediated lamivudine transport (IC 50 =13.2 μM) [18].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…All of the MDCK cell lines were cultured in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% heat-inactivated fetal bovine serum (FBS). Double-transfected MDCKII cell lines stably expressing human OCT1 or OCT2 and MATE1 transporters (MDCK-OCT1-MATE1 and MDCK-OCT2-MATE1), as well as the respective monotransfected cells (MDCK-OCT1, MDCK-OCT2, and MDCK-MATE1) and control vector cells (MDCK-Co), were established and characterized as described previously (17,21,22). Cells were cultured in MEM containing 10% heat-inactivated FBS.…”
Section: Methodsmentioning
confidence: 99%
“…The transcellular transport studies were performed as reported previously (22). Cells were seeded on transwell inserts (0.4 m, diameter of 12 mm) at a density of 2 ϫ 10 5 cells per insert for MDCK-hOCT2-hMATE1, MDCK-hOCT2, and MDCKhMATE1 and at 1 ϫ 10 5 cells per insert for mock-transfected cells to unify protein concentrations for different amounts of cell growth.…”
mentioning
confidence: 99%